Geoelectric structure of northern Cambay rift basin from magnetotelluric data - Danda, Nagarjuna; Rao, C. K.; Kumar, Amit (My University, 2017)
Broadband and long-period magnetotelluric data were acquired over the northern part of the Cambay rift zone along an east–west profle ~ 200 km in length. The decomposed TE- and TM-mode data were inverted using a 2-D nonlinear conjugate gradient algorithm to obtain the lithospheric structure of the region. A highly conductive (~ 1000 S) layer was identifed within the Cambay rift zone and interpreted as thick Quaternary and Tertiary sediments. The crustal conductors found in the profle were due to fuid emplacement in the western part, and the presence of fuids and/or interconnected sulfdes caused by metamorphic phases in the eastern part. The demarcation of the Cambay rift zone is clearly delineated with a steeply dipping fault on the western margin, whereas the eastern margin of the rift zone gently dips along the NE–SW axis, representing a half-graben structure. A highly resistive body identifed outside the rift zone is interpreted as an igneous granitic intrusive complex. Moderately conductive (30–100 Ω-m) zones indicate underplating and the presence of partial melt due to plume–lithosphere interactions.
Keywords: Cambay rift zone; Deccan basalt; Lithosphere; Magnetotellurics; Reunion plume